Budget Planning Based on the Interests of the Ummah - Nur Handayani; Maratus Zahro; Susanti Susanti (Perspektif Akuntansi, 2023)
The Revenue and Expenditure Budget Plan (RAPB) is an essential tool to be able to link between the planning and control processes within the organization. This research aims to determine the concept of budget planning carried out by TK Yaa Bunayya the Hidayatullah Islamic Boarding School. The research method used a qualitative method. The research result showed that The RAPB of the Hidayatullah Islamic Boarding School is compiled by units with the following stages: (1) preparation and ratification of the RAPB, (2) implementation of the RAPB, (3) accountability and reporting. The process of preparing the RAPB carried out by each unit in the Hidayatullah Islamic boarding school environment is based on the public interests of the ummah. “Ummah” according to the Hidayatullah Islamic Boarding School's perspective, are donors and people who use their services directly. Determination of work programs based on the interests of the ummah reflects the form of preparation of the RAPB that is right on target. The interests of the ummah become the basis for determining unit work programs that reflect common interests. This has an impact on the lack of conflicts that arise between the implementing unit and the foundation as the manager.